2021
DOI: 10.4103/jpbs.jpbs_838_20
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Periodontal Disease

Abstract: Background and Aims: In periodontal disease, pathogenic inflammatory factors hold a vital part in adverse pregnancy outcomes. In recent years, there has been a large amount of literature concerning the association between periodontal disease and adverse pregnancy outcomes such as preterm birth (PTB) and low-birth-weight baby (LBWB). In the Middle-east region, reports indicate a higher rate of adverse pregnancy outcomes, and periodontitis is believed to be one of several risk factors for adverse pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
2
0
4
Order By: Relevance
“…Complications during pregnancy and childbirth are among the leading causes of disease and death among women in reproductive age worldwide. 21 In the current study, less than a quarter (17.5%) reported adverse pregnancy outcomes, a recent study in Qassim also reported a similar prevalence of 17.9% 22 which was significantly associated with higher prevalence and severity of periodontal diseases in both studies. The evidence for such an association is increasing with the prevalence reported worldwide to be between 15% and 100%.…”
Section: Discussionsupporting
confidence: 54%
“…Complications during pregnancy and childbirth are among the leading causes of disease and death among women in reproductive age worldwide. 21 In the current study, less than a quarter (17.5%) reported adverse pregnancy outcomes, a recent study in Qassim also reported a similar prevalence of 17.9% 22 which was significantly associated with higher prevalence and severity of periodontal diseases in both studies. The evidence for such an association is increasing with the prevalence reported worldwide to be between 15% and 100%.…”
Section: Discussionsupporting
confidence: 54%
“…Alrumayh A. et al 2 recolectaron datos para su estudio a través de cuestionarios y exámenes orales, se tomó una muestra de 380 en edad gestacional de las cuales el 100% se relacionó con alguna enfermedad como (gingivitis 78,9% y periodontitis 21,1%) este estudio fue realizado en una región del medio oriente en asistían al Maternal and Children's Hospital en Buraidah.…”
Section: Iiiresultadosunclassified
“…Alrumayh A. et al 2 Evidencio una prevalencia completa de enfermedad periodontal la cual es un factor de riesgo en el embarazo ya que presenta una prevalencia elevada. Conceição SDS.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Inflammation of the gingival tissue is more common in women with a history of hormonal contraception compared to other types of contraception. The hormones progesterone and estrogen also impact decreasing the response of the gingival tissue and oral cavity and changes in the population of microorganisms and feelings of discomfort in the mouth (Alrumayh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%